Is social entrepreneurship a panacea for sustainable enterprise development? - Asad Javed; Muhammad Yasir; Abdul Majid (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2019)
The purpose of this empirical study is to examine the relationship between social entrepreneurship and sustainable enterprise development. Four dimensions of social entrepreneurship i.e. social mission, social innovation, social networking, and financial returns are regressed with three dimensions of sustainable enterprise development i.e. social, environmental, and economic. In current literature, most of the work in the field of social entrepreneurship is qualitative in nature and none of the existing studies explained the impact of labeling "social enterprise" as a source of enterprise sustainability and this study used positivist paradigm to test this impact. Data was collected from social entrepreneurs and employees of social enterprises via online questionnaire (n=434) developed and distributed through "Google Docs". Social entrepreneurs from 41 different countries participated in online survey. The results of the study reveal that social entrepreneurship results in sustainable enterprise development. The study supports the fact that one of the important factors in enterprise development is the way the enterprise is managed and the label of "social enterprise‟ is resulting in sustainable development of social enterprise itself. The research contributes to literature by empirically testing the relationship between social entrepreneurship and sustainable enterprise development which was never tested before. The study used a unique methodology that results in gathering of data from 41 countries of the world. This results of this study can be used by social entrepreneurs to create more positive impact for the society.
Keywords: 330; social entrepreneurship; social mission; social networks; social innovation; financial returns; sustainable enterprise development; social sustainability; environmental sustainability; economic sustainability